2003
DOI: 10.1016/s0265-931x(03)00052-3
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon (222Rn) concentration measurements in Cyprus using high-sensitivity portable detectors

Abstract: Using high-sensitivity radon ( 222 Rn) portable detectors (passive electronic devices of the type RADIM3), the airborne 222 Rn concentration in the interior of various Cypriot buildings and dwellings was measured. For each preselected building and dwelling, a calibrated detector was put into a closed room, and the 222 Rn concentration was registered in sampling intervals of 2 to 4 hours for a total counting time of typically 48 hours. 222 Rn activity concentrations were found to be in the range of 6.2 to 102.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
6
29
0
Order By: Relevance
“…A pilot project was therefore initiated aiming at systematically measuring the terrestrial gamma radiation in Cyprus and at determining its contribution to the annual effective dose equivalent to the population. Other part of the project includes measurement of radon concentration in houses and public buildings (Anastasiou et al, 2002) as well as the detection of α−emitting radioisotopes by utilizing radioanalytic techniques and high-resolution α-spectroscopy. In this paper, the first results from natural gamma radiation measurements in all the types of geological rock formations appearing in Cyprus (Figure 1) are presented.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot project was therefore initiated aiming at systematically measuring the terrestrial gamma radiation in Cyprus and at determining its contribution to the annual effective dose equivalent to the population. Other part of the project includes measurement of radon concentration in houses and public buildings (Anastasiou et al, 2002) as well as the detection of α−emitting radioisotopes by utilizing radioanalytic techniques and high-resolution α-spectroscopy. In this paper, the first results from natural gamma radiation measurements in all the types of geological rock formations appearing in Cyprus (Figure 1) are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Other parts of the project aimed at measuring the concentration of radon in houses and public buildings (Anastasiou et al, 2003), as well as at detecting α−emitting radioisotopes by utilising radioanalytical techniques and high-resolution α-spectrometry (Pashalidis and Tsertos, 2003). In this paper, the results from this extensive survey regarding Th, U and K elemental concentrations in a wide variety of surface soils by means of high-resolution γ−ray spectrometry are presented.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, Anastasiou et al (2003) reported that a basement and underground space directly in contact with soil show higher radon concentrations in the airthan other spaces. Li et al (2005) suggested that indoor ventilation is one of the major factors that greatly influence the radon concentration in indoor air.…”
Section: Research Related To Radon Concentrations In Koreamentioning
confidence: 99%